Identificación, Reforestación y Protección De Nacimientos De Agua En El Municipio De Vergara Cundinamarca (2022)
This document provides information on the phase of identification and reforestation of springs in the municipality of Vergara Cundinamarca, allowing to have a vision on the management of water resources, the current state of springs and the effects presented to springs to the width of the territory, allowing the integration of the population, contributing to the improvement of the quality of life and the conservation of the natural resources of the municipality. This document provides information on the phase of identification and reforestation of springs in the municipality of Vergara Cundinamarca, allowing to have a vision on the management of water resources, the current state of springs and the effects presented to springs to the width of the territory, allowing to integrate the population, contribute to the improvement of the quality of life and the conservation of the natural resources of the municipality.